ANALYSIS OF SERVANT LEADERSHIP AND TRANSFORMATIONAL LEADERSHIP ON AFFECTIVE COMMITMENT : A MEDIATION OF PERSON ORGANIZATIONAL FIT - Listyaningrum, Palupi; Hadi, Syamsul; Purnamarini, Tri Ratna (International Conference on Humanity Education and Society (ICHES), 2024)
Affective commitment is an attachment of emotional feelings from employees who can contribute to the organization that can lead to good behavior in an effort to improve organizational performance. This study aims to analyze the influence of servant leadership and transformational leadership on affective commitment mediated by person organizational fit. This study used quantitative methods with purposive sampling techniques involving 51 respondents in the Regional Inspectorate of Bantul Regency, while processing data using SmartPLS version 4.0. The results showed that servant leadership and transformational leadership were not proven to have a positive effect on affective commitment, but servant leadership and transformational leadership were proven to have a significant positive effect on person organizational fit, person organizational fit had a significant positive effect on affective commitment and able to mediate between servant leadership and transformational leadership on affective commitment.